LC3-Associated Phagocytosis Is Required for Dendritic Cell Inflammatory Cytokine Response to Gut Commensal Yeast Saccharomyces cerevisiae - Lamprinaki, Dimitra; Beasy, Gemma; Zhekova, Aleksandra; Wittmann, Alexandra; James, Steve; Dicks, Jo; Iwakura, Yoichiro; Saijo, Shinobu; Wang, Xiaomin; Chow, Chung-Wai; Roberts, Ian; Korcsmaros, Tamas; et al. (Frontiers in Immunology, 2017)
The human fungal microbiota known as mycobiota is increasingly recognized as a critical factor in human gut health and disease. Nonpathogenic commensal yeasts such as Saccharomyces cerevisiae promote homeostasis in the gut, whereas dysbiosis of the gut mycobiota is associated with inflammation. Glycan-binding receptors (lectins) are key host factors in host-mycobiota interaction in the gut. They are expressed on immune cells such as dendritic cells (DCs) and recognize fungal polysaccharides. This interaction is imperative to mount appropriate immune responses for immune homeostasis in the gut as well as clearance of fungal pathogens. Recent studies demonstrate that microtubule-associated protein light-chain 3 (LC3)-associated phagocytosis (LAP) is involved in lectin-fungi interactions. Yet the biological impact of LAP on the lectin function remains largely elusive. In this report, we demonstrate that in mouse LAP is linked to Dectin-2, a C-type lectin specific to fungal -mannan polysaccharide. We found that mouse Dectin-2 recognizes commensal yeast S. cerevisiae and Kazachstania unispora. Mouse bone marrow-derived DCs (BMDCs) produced inflammatory cytokines TNF and IL-1 in response to the yeasts in a Dectin-2 and Syk dependent manner. We found S. cerevisiae and K. unispora induced LAP in mouse BMDCs upon internalization. Furthermore, LC3 was activated by stimulation of BMDCs with the yeasts in a Dectin-2 and Syk-dependent manner. To address the biological impact of LAP on Dectin-2-yeast interaction, we established a knock-in mouse strain (Atg16L1E230, thereafter called E230), which BMDCs exhibit autophagy-active and LAP-negative phenotypes. When stimulated with yeasts, E230 BMDCs produced significantly less amounts of TNF and IL-1. Taken together, we revealed a novel link between Dectin-2 and LAP that enables host immune cells to respond to mycobiota.